Braiding A/r/tography & Métissage: Thinking together on the work of Sonny Assu - Rallis, Nicole; Leddy, Shannon; Irwin, Rita L. (Canadian Review of Art Education / Revue canadienne d'éducation artistique, 2024)
Three art educators come together to respond to the work of Sonny Assu, Ligwilda’xw of the Kwakwaka’wakw Nations, who was invited as an artist-in-residence to a graduate seminar on Indigenous visual expression as pedagogy. Engaging with the concepts of Indigenous métissage, diffraction, and a/r/tography, we weave together our personal stories, identities, and practices. We discuss ways to engage in anti-colonial teaching practices that provide openings for students to retrace, reimagine, and reconcile their understandings of Indigenous-settler relations in Canada. Our call to action asks art educators to consider Indigenous métissage as an important diffractive research practice and pedagogical praxis.